"The doctor was rude, the toilets are dirty. Utilizing 'soft signals' in the regulation of patient safety". (November 2020) - Kok, Josje; Wallenburg, Iris; Leistikow, Ian; Bal, Roland
Highlights: Healthcare is highly data- and evidence driven, there is a dominant 'measure and manage' attitude. But, there are calls that 'soft signals' too are vital to assess quality and safety. We show how healthcare inspectors use soft and hard signals in their assessments. We argue that what is recognized as 'hard' and 'soft' is not always so clear-cut. Rather, these labels are layered and the outcome of sensemaking practices. Abstract: Modern healthcare systems are highly data- and evidence-driven. The use of indicators and other performance management devices, introduced by healthcare leaders and regulators to monitor performance and address patient safety matters, are just two examples. Research has shown that the wish to manage and address risks via measuring practices does not always do justice to the complexities of healthcare organization and delivery, for (patient) safety and quality are not only about measurable things. So, while recognized as valuable, there are calls that hard metrics must be supplemented with soft signals – generally known as qualitative or informal data – to gain a better representation of actual performance and tackle safety issues. With the aim to contribute to the theoretical notion that a dialogical approach to knowledge and information-management is a fruitful way to manage and address risks and problems in healthcare, this paper addresses the research question 'What role do soft signals play in the assessment of patient safety risks and how are these signals employed in everyday regulatory practices?' We draw from qualitative interviews, observations and document analyses in a multi-year (2015–2019) research project to show that soft signals are vital to everyday regulatory practices, as they provide context to 'hard' signals and help to make sense of and weigh risks. Based on these findings we encourage policy makers and regulatory bodies to start an active dialogue on their use of soft signals and develop work models and working routines for discussing them as well as their implications.